5z-6+6=-36+z

Simple and best practice solution for 5z-6+6=-36+z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5z-6+6=-36+z equation:


Simplifying
5z + -6 + 6 = -36 + z

Reorder the terms:
-6 + 6 + 5z = -36 + z

Combine like terms: -6 + 6 = 0
0 + 5z = -36 + z
5z = -36 + z

Solving
5z = -36 + z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-1z' to each side of the equation.
5z + -1z = -36 + z + -1z

Combine like terms: 5z + -1z = 4z
4z = -36 + z + -1z

Combine like terms: z + -1z = 0
4z = -36 + 0
4z = -36

Divide each side by '4'.
z = -9

Simplifying
z = -9

See similar equations:

| 9a+2a-8a-3b= | | 29b-93=7 | | 5(2x-10)/2 | | 3x+7=9x+5 | | 4v^2+25v+21=0 | | 16a+8b+1=0 | | 12-b=0 | | (-7b-2c)+(6b-3c-1)= | | X+3x+(x+7)=32 | | 8a(-3a)= | | 50=1.75x | | -((-3)+3)= | | 5x+8=9x-8 | | 16a+8a+1=0 | | b(b-3)=28 | | 0=-16x^2+1400 | | 12=780x | | 6x-46=4x+76 | | 19+1=20 | | 1600=-4x | | 6x+2+3x=74 | | x^4+5x^3+7x^2-4=0 | | -5(6b-8)=30-9b | | f(x)=-2x^3-4x^2-1 | | 7y/10-18=7/17/40 | | -8n-7n=29 | | -4(5+8y)=-17 | | 18x-10+9xz-5z=0 | | -34=-6a+8a | | 0=1.5x^2-4x | | 6x+5ab=7x-9ab | | -9c-5-3c=-32 |

Equations solver categories